OPTIMALISASI MANAJEMEN PEMBIAYAAN UNTUK MENINGKATKAN KINERJA BANK SYARIAH - Marsyah Aprilya; Yeni Aprilina Pulungan; Muhammad Ikhsan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the challenges, strategies, and impacts of optimizing Islamic financing management in Islamic banks, focusing on Sharia compliance, managerial effectiveness, product optimization, and the role of Islamic Corporate Governance (ICG). Using a qualitative library research method, this study examines theories, financial reports, and previous literature related to Islamic financing management. The results indicate that effective financing management supported by digitalization, strengthened managerial capacity, and compliance with Sharia principles improves financial performance, reduces non-performing financing, supports sustainable growth, and enhances social welfare through productive and ethical financing. The study concludes that the integration of Sharia values, strong governance, and technological innovation is essential for achieving competitive and sustainable Islamic banking performance